A study of interceptor performance for deep-v planing hull. Issue 1 (1st September 2022) - Samuel, S.; Yulianti, Serliana; Manik, Parlindungan; Fathuddiin, Abubakar
Abstract: The acting on the planing hull is the most complex hydrodynamics simulation. Therefore, an analysis was done to evaluate drag, lift force, and seakeeping in two degrees of freedom (2-DOF) which is heave and trim. It was fundamental aspects of the overall high-speed vessel. This article focused on the hydrodynamic performance of a complete interceptor configuration that could control the motion behavior of deep-V planing hull in calm water conditions. The benchmark study was undertaken by comparing numerical results with experimental study by Park at al. Models with and without interceptors had been analyzed by numerical simulation performed using Reynold Averaged Navier Stokes (RANS) to describe turbulence model with k epsilon based on computational fluid dynamic (CFD). In this study, the interceptor proper applies at a speed of less than Froude number 0.87. Interceptor reduce by 21% drag at Froude number 0.87 and also reduce by 16% trim and 6% heave at Froude number 0.58. Nevertheless, applied interceptor in high Froude number such as more than Froude number 1.16 caused interceptor lose effectiveness due to producing a decisive moment which made negative trim (bow-down) and increase total drag.